Evaluation of Aetiological Factors and Outcome of Cholelithiasis in Children: Experience in Tertiary Level Hospitals - Khan, Shams Ud Din Elias; Rahman, Md Mahbubur; Khan, AR; Amin, Md Ruhul; Aziz, Md Abdul; Parveen, Zinia (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Gallstone disease is frequently reported in children in last few decades due to widespread use of ultrasonography (USG) as diagnostic tool. There may be absolute increase in number because of increased use of Total Parenteral Nutrition (TPN), ileal resections and use of certain drugs like Ceftriaxone. Traditionally childhood cholelithiasis is classified as haemolytic or non haemolytic in origin. Objectives:To share this experience about the aetiology and outcome of childhood cholelithiasis. Material and Methods: This observational study was carried out in the Department of Paediatric Surgery, Combined Military Hospital (CMH) Dhaka, Dhaka Shishu Hospital (DSH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of January 2016 to December 2018. Results: During the study period a total of 65 children with childhood cholelithiasis were treated in 3 major hospitals of Dhaka city (CMH Dhaka-35, DSH-15, and BSMMU-15) and included 29(44.62%) male and 36(55.38%) female children making a female to male ratio of 1.24:1. There were 23(35.38%) children in the asymptomatic group and 42(64.62%) in the symptomatic group. In this study haemolytic anaemia was present in 12(18.46%) children with gallstone disease and 53(81.54%) were in non haemolytic group. Gallstone dissolved in 17(26.15%) children in subsequent follow up within 6 months and 48(73.85%) required operative treatment. Conclusion: Childhood cholelithiasis is being recognized with increased frequency recently. So cholelithiasis should be excluded in all cases of vague, intermittent abdominal pain in susceptible paediatric age group. Childhood cholelithiasis has less chance of complication and high rate of resolution. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 140-143